The Culture of Organisational Involvement and the Psychosocial Needs of Employees - Krzyżak, Joanna; Motyka, Marek (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
From a psychological point of view, all human activities are motivated by key needs of the individual, be they biological, economic or psychosocial. As living standards improve, the latter factors become increasingly important. Consequently, successful employee motivation is becoming more and more dependent on complex psychosocial reinforcements. The authors of this article seek to emphasise the issue of employees’ internal motivation, which is often underestimated in practice. In particular, much attention is devoted to the importance of incorporating core psychosocial needs of employees into the company’s organisational culture, as the authors believe it to be a key factor contributing to organisational involvement.